Secreted int-1 protein is associated with the cell surface. - Papkoff, J (1990)
The murine int-1 proto-oncogene has been implicated in neural development and, when transcriptionally activated by mouse mammary tumor virus, contributes to the genesis of mammary tumors. To understand the function of the int-1 gene product in these processes, we have characterized the biochemical properties of int-1 protein expressed in a neuroendocrine cell line transfected with int-1 cDNA. Here we provide evidence that int-1 protein is secreted and associates with the cell surface. int-1 protein was very efficiently processed and secreted through the constitutive secretory pathway, although no int-1 protein could be immunoprecipitated from the culture medium. Treatment with suramin effectively released mature int-1 proteins into the culture fluid, which suggests that secreted int-1 protein associates with the cell surface or extracellular matrix. We have also shown directly, by radioiodination of intact cells and by surface antibody adsorption, that secreted int-1 proteins can be detected on the cell surface. These data support a model in which int-1 protein is secreted and functions locally in cell-to-cell signaling.